PLOT AND COMPOSITION IN THE INTERPRETATION OF REALITY AND LIFE: A POETIC ANALYSIS OF OMON MUXTOR’S SHORT STORIES (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article provides a scholarly analysis of the plot and compositional structure in the short stories “Adabiyot muallimi” (The Literature Teacher), “Mezon” (The Criterion), and “Qorboboning qaytishi” (The Return of Father Frost) by the Uzbek writer Omon Muxtor. The plot is explored not merely as a sequence of simple events, but as an artistic system shaped by the author’s aesthetic purpose. Composition, in turn, is considered as the internal and external structure that elevates this system into an integral artistic whole. The research focuses on the personal destiny, spiritual quest, and social role of the protagonists, revealing the harmony between symbolic layers and real-life events. In “Adabiyot muallimi”, the parallel construction of symbolic narration and contemporary reality is highlighted; in “Mezon”, the fusion of philosophical monologue and retrospective composition is analyzed; and in “Qorboboning qaytishi”, the transformation of a seemingly simple storyline into a profound philosophical reflection is elucidated. In conclusion, these stories are evaluated as vivid examples of the unity of plot and composition in Uzbek short fiction.